17 librarians and one big undertaking: creating a digital project from start to finish. Issue 1 (2nd March 2020) - Hartsell-Gundy, Arianne; Lawton, Kelley; Rozear, Hannah
Abstract: As academic librarians prepare for new forms of collaboration with researchers on digital projects, there is a growing demand for librarians to acquire skills with project management, as well as specific digital tools and methods. This article describes how research librarians collaborated together to complete a digital project related to student activism in the 1930s and 1940s on their campus. From researching in the archives to creating a digital timeline, the project utilized a team-based, "learn by doing" approach to allow librarians the opportunity to work through the logistics of a project from start to finish. The organization of the project, the digital tools and methods used, and the lessons learned are described in detail.